Association Between Dietary Total Antioxidant Capacity and Diet Quality in Adults - Salari-Moghaddam, Asma; Nouri-Majd, Saeedeh; Keshteli, Ammar Hassanzadeh; Emami, Fatemeh; Esmaillzadeh, Ahmad; Adibi, Peyman (Frontiers in Nutrition, 2022)
Background Diet quality is a major contributor to human health. In addition, antioxidants have a great contribution to several chronic conditions. The purpose of this study was to evaluate if dietary total antioxidant capacity (TAC) can be considered as a measure of diet quality in a Middle Eastern country. Methods In this cross-sectional study on 6,724 Iranian adults, we used a validated food frequency questionnaire (FFQ) to assess dietary intakes. Data derived from the FFQ was used to calculate dietary TAC and well-known diet quality scores including alternate healthy eating index (AHEI) and dietary diversity score (DDS). Dietary TAC was calculated based on the ferric reducing-antioxidant power (FRAP) values reported in earlier publications. AHEI and DDS have also been constructed based on previous publications. Cross-classification was used to examine the agreement between these measures. Results Mean age and BMI of study participants were 36.89 ± 8.08 y and 24.97 ± 3.87 kg/m2, respectively. We found that individuals in the highest tertile of dietary TAC had higher scores of AHEI (57.53 ± 0.20 vs. 52.03 ± 0.20, P < 0.001) and DDS (5.56 ± 0.03 vs. 4.15 ± 0.03, P < 0.001) compared with those in the lowest tertile. Participants' distribution on the basis of the cross-classification analysis indicated that the classifications were in exact agreement for 42.6%, within an adjacent tertile for 33.05%, and in gross misclassification for 20% of individuals. When this was examined between dietary TAC and DDS, we found that exact agreement in the classifications was for 59.2% of participants. Notably, a very low proportion of gross misclassification was seen in this regard such that only 6% of participants were classified in the opposing tertiles, indicating additional support for a good agreement. Conclusion We found that dietary TAC might be considered as a proper measure for the assessment of diet quality because it was well correlated with well-known measures of diet quality including DDS and AHEI scores.